The Effect of Financial Performance on Stock Returns in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015-2024 Period - Munadyah Munadyah; Hety Budiyanti; Annisa Paramaswary Aslam; Anwar Anwar; Nurman Nurman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of financial performance, proxied by Current Ratio (CR), Return on Assets (ROA), and Total Assets Turnover (TATO), on stock returns. The research object consists of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2015–2024 period. The sampling technique used was purposive sampling, resulting in 12 companies that met the research criteria. The partial test results (t-test) show that: (1) Current Ratio (CR) has a significant negative effect on stock returns, (2) Return on Assets (ROA) has a significant positive effect on stock returns, and (3) Total Assets Turnover (TATO) has a significant negative effect on stock returns. Meanwhile, the simultaneous test results (F-test) indicate that CR, ROA, and TATO together have a significant effect on stock returns. These findings indicate that profitability (ROA) is the most dominant factor influencing stock returns. However, the market also provides a negative response to inefficiencies in liquidity management (CR) and asset turnover (TATO). Therefore, companies are encouraged to maintain a balance between liquidity, profitability, and asset utilization efficiency to enhance shareholder value.